School days - Parker, Robert B., 1932- (New York : G.P. Putnam's Sons, 2005)
Hired by a Massachusetts grand dame to prove the innocence of her grandson, who has been implicated in a school shooting, Spenser wonders why the boy seems unconcerned about his possible wrongful imprisonment.
Keywords: Spenser (Fictitious character) -- Fiction; Private investigators -- Massachusetts -- Boston -- Fiction; Boston (Mass.) -- Fiction; Mystery fiction